2010
DOI: 10.1103/physrevlett.105.246803
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Anisotropic Dirac Cones in Epitaxial Graphene Modulated by an Island Superlattice

Abstract: We present a new method to engineer the charge carrier mobility and its directional asymmetry in epitaxial graphene by using metal cluster superlattices self-assembled onto the moiré pattern formed by graphene on Ir(111). Angle-resolved photoemission spectroscopy reveals threefold symmetry in the band structure associated with strong renormalization of the electron group velocity close to the Dirac point giving rise to highly anisotropic Dirac cones. We further find that the cluster superlattice also affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 26 publications
2
120
1
Order By: Relevance
“…3 exhibit replicas with the periodicity of the Moiré structure. This contrasts, e.g., with recent observations for graphene on a metallic substrate, 15,16 where the Moiré structure gives rise to folded bands, with intensities proportional to the strength of the superlattice potential.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…3 exhibit replicas with the periodicity of the Moiré structure. This contrasts, e.g., with recent observations for graphene on a metallic substrate, 15,16 where the Moiré structure gives rise to folded bands, with intensities proportional to the strength of the superlattice potential.…”
Section: Resultscontrasting
confidence: 89%
“…[1][2][3] Characteristic signatures of superperiodicities have been observed by ARPES in bulk materials [4][5][6] and at ordered interfaces. [7][8][9][10][11][12][13][14][15][16] Lead overlayers on both metallic and semiconducting substrates are especially interesting in this respect. It is found that, due to their high lateral stiffness, monolayers (ML) of Pb form dense Moiré superstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the chemical inertness of graphene itself and the low solubility of carbon in the Ir bulk, the growth process is self-limiting and always leads to one, and only one, layer of graphene [12]. The chemical interaction between the Ir substrate and graphene is rather weak, as evidenced by a nearly unperturbed band structure [13,14] and a long vertical distance between the C and Ir atoms [20], in contrast to other systems such as graphene/Ni(111) or graphene/Ru(0001), where the strong hybridization of electronic bands opens up a gap in the Dirac cone. In addition, graphene on Ir(111) is nearly undoped, whereas for example graphene on SiC(0001) shows strong n-doping as a result of charge transfer between graphene and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For the coverage used in this experiment, the mean cluster size is 13 atoms. Apart from the interest of such clusters in catalysis and for seeding of magnetic materials, these clusters act as point scatterers for the electrons in the underlying graphene and lead to a band gap of 0.34 eV, while fully preserving the graphene electron group velocities, a necessary condition for the high charge carrier mobilities required in applications [34]. A similar effect has been obtained by H adsorption on specific sites of the moiré pattern [186].…”
Section: Heterogeneous Nucleationmentioning
confidence: 54%
“…A topical example is the CVD growth of graphene on single-crystal metal surfaces, which we only briefly discuss here, as more details are given in Chapter 25 of this volume. The carbon containing molecules are, for example, ethylene [31][32][33][34][35] and ethene [36][37][38]. At most metal surfaces, C 2 H 4 deprotonates to ethylidene (C 2 H 3 ) already at 300 K [31,39]; above 430 K, further dehydrogenation occurs, until, at 700 K, only chemisorbed C atoms remain at the surface.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%